Implementación de herramientas CFD para la optimización del proceso de secado de lámina en la línea de decapado de la Empresa Acesco y CIA SCA. (2011)
This applied research paper describes the implementation of CFD (Computational Fluid Dynamics) tools for optimization of the sheet drying process in the company Acesco and CIA SCA, where it is difficult to perform field experiments because the execution of the runs would represent an obstacle to production schedules in the industry. Methodologically, the most relevant variables to the process were identified in the first place, in order to establish the factors and the response variable(s) involved in the experiment, and then the runs were performed in the simulation software to finally analyze the results using statistical software in order to find the treatment that minimizes the water content on both sides of the sheet. By using the statistical software Statgraphics, the results were optimized and it was found that the optimal combination of variables correspond to a low sheet speed with a medium air mass flow. Contrary to the expected, a higher hot air mass flow does not represent the best drying results.